2017
DOI: 10.1108/jacpr-05-2017-0296
|View full text |Cite
|
Sign up to set email alerts
|

Risky sex: testing moderated mediation among college students

Abstract: Purpose Risky sexual behavior (RSB) on college campuses contributes to elevated rates of sexually transmitted infections and sexual assault. Research indicates a positive association between sexual victimization history (SVH) and RSB with alcohol use and sexual sensation seeking as mediators to this association. Hypermasculinity has also been shown to play a moderating role amongst these associations. Therefore, the purpose of this paper is to test the associations between RSB, SVH, alcohol use, sexual sensati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 51 publications
(72 reference statements)
1
2
0
Order By: Relevance
“…Results indicated adolescents identifying as female, non-White, and LGBQ were more likely to report experiencing physical TDV and sexual TDV than their male, White, heterosexual peers, aligning with prior research findings (Hipwell et al, 2013;Kann et al, 2016;Vagi et al, 2015). This may be reflective of toxic masculinity/hypermasculinity in TDV perpetration, influencing who experiences TDV (Silverstein et al, 2017), as males who have hypermasculine traits may be more likely to target more marginalized and vulnerable persons. Beyond main effects, there were differences in intersectional identity by TDV experience.…”
Section: Discussionsupporting
confidence: 78%
“…Results indicated adolescents identifying as female, non-White, and LGBQ were more likely to report experiencing physical TDV and sexual TDV than their male, White, heterosexual peers, aligning with prior research findings (Hipwell et al, 2013;Kann et al, 2016;Vagi et al, 2015). This may be reflective of toxic masculinity/hypermasculinity in TDV perpetration, influencing who experiences TDV (Silverstein et al, 2017), as males who have hypermasculine traits may be more likely to target more marginalized and vulnerable persons. Beyond main effects, there were differences in intersectional identity by TDV experience.…”
Section: Discussionsupporting
confidence: 78%
“…Participation in risky sexual behavior varies across sex and racial and ethnic identity. Research broadly demonstrates that men are more likely to report engaging in risky sexual behavior compared with women (Fix et al, 2019;Silverstein et al, 2017). In addition, reported rates of risky sexual behavior are often higher among African American and Latinx Americans compared with White Americans (Fix et al, 2019).…”
Section: Aces Mental Health and Risk Behaviorsmentioning
confidence: 99%
“…This measure accounts for RSB that occurs while under the influence of alcohol or a person’s expectations about sexual behaviors while under the influence of alcohol. A recent study of college men and women found that alcohol use mediated the relationship between sexual victimization and RSB (Silverstein, Fix, & Alexander, 2017). Thus, future research should investigate this relationship and consider alcohol use as a mediating variable between polyvictimization and RSB.…”
Section: Discussionmentioning
confidence: 99%